2015
DOI: 10.1177/0020764015597951
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar risk and mental imagery susceptibility in a representative sample of Chinese adults residing in the community

Abstract: Background:We need to better understand the cognitive factors associated with risk for bipolar disorders. Recent research suggests that increased susceptibility to mental imagery may be one such factor. However, since this research was primarily conducted with Western students and at a single time-point, it is not known whether the relationship between imagery susceptibility and bipolar symptoms exists across cultures or within the general community, or whether this relationship remains stable over time.Aim:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Our results on the association between BD phenotype and affective lability traits, and greater imagery frequency and emotionality, are in keeping with previous findings that individuals with a BD phenotype are more susceptible to intrusive imagery and to spontaneous use of imagery . Interestingly, better performance in imagery maintenance via visual short‐term memory was also associated with affective lability.…”
Section: Discussionsupporting
confidence: 91%
“…Our results on the association between BD phenotype and affective lability traits, and greater imagery frequency and emotionality, are in keeping with previous findings that individuals with a BD phenotype are more susceptible to intrusive imagery and to spontaneous use of imagery . Interestingly, better performance in imagery maintenance via visual short‐term memory was also associated with affective lability.…”
Section: Discussionsupporting
confidence: 91%
“…Our data are more consistent with the notion that imagery-based abnormalities reflect (neuro)cognitive markers of the disorder itself—abnormalities that are likely to play a role in increasing future relapse given their persistence in remitted states. We note that previous research has shown altered emotional mental imagery in individuals with phenotypic (rather than genetic/familial) risk for BD, mainly based on the presence of hypomanic-like experiences (32, 43, 69, 79). However, our study was the first to focus instead on genetic-based risk using a twin design enabled by the unique Danish registers (49).…”
Section: Discussionmentioning
confidence: 65%
“…However, our study was the first to focus instead on genetic-based risk using a twin design enabled by the unique Danish registers (49). As a potential explanation for this discrepancy, maladaptive prospective emotional imagery may be associated with phenotypic characteristics of affective disorders that lie on the same dimension of clinical symptoms, such as the actual presence of dysphoric mood (47, 62) or hypomanic-like experiences (32, 43, 69, 79), but we did not measure such features in our high-risk twins. Another potential explanation is that our high-risk twins had an average higher age compared to at-risk groups from previous research.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, patients with bipolar disorders reported experiencing more vivid, exciting and pleasurable 'flash-forwards' (future images) at times of positive mood compared to patients with unipolar depression (Ivins, Di Simplicio, Close, Goodwin, & Holmes, 2014). Higher imagery susceptibility was also found in people with high hypomanic experiences (measured on the Mood Disorders Questionnaire; Malik, Goodwin, Hoppitt, & Holmes, 2014;Ng, Burnett Heyes, McManus, Kennerley, & Holmes, 2015), something we are following up in a familial risk study. Thus, there is to date some preliminary support that people with a bipolar phenotype are more likely to visualise their thoughts and also report stronger emotional arousal to their own visual images than people without a bipolar phenotype.…”
Section: Mental Imagery Susceptibility and Bipolar Disordersmentioning
confidence: 93%